FACTORS OF DECISION MARKING OF THAI TOURISTS’ TRAVELING TO LAMPRAYA MARKET NAKHON PATHOM - Chutima Nootayasakul ชุติมา นุตยะสกุล; Prasopchai Pasunon ประสพชัย พสุนนท์ (Dusit Thani College Journal, 2018)
The purposes of this research were to study 1) to study factors of decision making of Thai tourists’ traveling To Lampraya Market. Nakhon Pathom and 2) to understand the behavior of tourists at Lampaya market, Nakhon Pathom, Data were collected by questionnaire from a sample of 400 Thai tourists who traveled to lampaya market. Factor analysis and cluster analysis techniques used for data analysis. The results showed that 1) the decision of thai tourists, consisted of 8 factors with a focus on the factors of service. It was followed used by the Tourist Information Center, Facilities, values and lifestyles, incentives and price, respectively. 2) The Behavior of tourists was divided into 4 groups : 1. Those emphasizing on values, living patterns and safety in tourism. 2. Those focusing on safety and tourist attractions particular on information 3. Those beging interested in tourist sights, price of merchandise ,values and lifestyles. 4. Those interested in tourist sites, safety values and lifestyle and particular facilities met in those sites.